2014
DOI: 10.2169/internalmedicine.53.1970
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment with Entecavir for Reactivation of Hepatitis B Virus Following Systemic Chemotherapy in a Hepatitis B Surface Antigen-negative Patient with Colorectal Cancer

Abstract: Reactivation of hepatitis B virus (HBV) has recently been reported as a fatal complication in patients undergoing cytotoxic chemotherapy. We herein describe a case of reactivation in a 76-year-old man who had undergone pelvic exenteration for colorectal cancer (CRC). He was treated with a modified FOLFOX6 chemotherapy regimen after the operation. Thirteen months later, his laboratory data showed severe liver dysfunction. His hepatitis B surface antigen (HBsAg) test was positive, and his HBV-DNA level was eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Furthermore, hepatitis B in patients with CRC is reported to reduce the risk of liver metastasis with simultaneous increase in extrahepatic metastasis 29. Furthermore, chemotherapy is reported to reactivate hepatitis B in patients with CRC, who were HBsAg-negative previously 30. Hence, telbivudine (600 mg qd) was administered throughout the chemotherapeutic period to obtain the optimal effects of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hepatitis B in patients with CRC is reported to reduce the risk of liver metastasis with simultaneous increase in extrahepatic metastasis 29. Furthermore, chemotherapy is reported to reactivate hepatitis B in patients with CRC, who were HBsAg-negative previously 30. Hence, telbivudine (600 mg qd) was administered throughout the chemotherapeutic period to obtain the optimal effects of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence of a link between surgery‐induced immunosuppression and PHR may extend to various types of surgery beyond hepatic resection. Indeed, several studies have reported that PHR can occur following TACE, RFA, or chemotherapies , as well as after partial hepatectomy and organ transplantation . Future studies should explore the link between immunosuppression and PHR in gastrectomy for gastric carcinoma, resection for bowel cancer and other surgeries besides hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous case reports and series describe death due to liver failure despite the introduction of lamivudine at the onset of HBVr [82][83][84][85][86] . Only a few cases of successful treatment of HBVr with entecavir have been published [87][88][89] .…”
Section: Management Of Hbvrmentioning
confidence: 99%